Religious and Pedagogical Education in Theology Faculties in Türkiye in Their 100th Year: A Comparative Analysis with Similar Programs in the World - Ahmet Koç (Religions)
This study compares religious education and pedagogy programs in theology faculties in Türkiye in their 100th year with similar programs in different countries. Although Türkiye historically has a deep-rooted heritage, it has experienced continued modernization for nearly two centuries. Various approaches were adopted in religious education during this process, and education policies were shaped accordingly. This situation shows that Türkiye’s religious education and pedagogical programs have continuously transformed in line with historical and social dynamics and are still open to development. When religious education and pedagogical programs in different countries were examined, it was determined that, although the programs have their purposes, such as acquiring religious knowledge, developing critical thinking, and training teachers, they show great diversity in their forms of application and content. When compared to examples around the world, it is evident that religious teachers in Türkiye start their profession with less pedagogical training than their colleagues both in Türkiye and abroad. In this regard, the first issue to be discussed is the review and updating of the curriculum. Another issue is structuring the course content to meet today’s needs and solve social problems. In addition, it is necessary to ensure that contemporary educational approaches are integrated into all undergraduate courses and that a holistic approach is applied.